2012
DOI: 10.1016/j.labeco.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The family gap in wages: What wombmates reveal

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 38 publications
1
10
1
1
Order By: Relevance
“…The younger the child, the more services were required: children less than 2 years old had an average of seven services per year, while children between 2 and 5 had an average of six services per year and children older than 6 had an average of three services per year. That children are less sick with age agrees with the negative correlation between mother's absenteeism and child age that was found by Simonsen and Skipper (2012). Next, we will examine whether mothers' earnings power is correlated with the fm.…”
Section: [Insert Figure 1 Here]supporting
confidence: 56%
See 1 more Smart Citation
“…The younger the child, the more services were required: children less than 2 years old had an average of seven services per year, while children between 2 and 5 had an average of six services per year and children older than 6 had an average of three services per year. That children are less sick with age agrees with the negative correlation between mother's absenteeism and child age that was found by Simonsen and Skipper (2012). Next, we will examine whether mothers' earnings power is correlated with the fm.…”
Section: [Insert Figure 1 Here]supporting
confidence: 56%
“…Using U.S. data, Pal and Waldfogel (2014) found that mothers in 2007 were doing no better than mothers in 1977, since the family gap had remained constant at 5-6%. Even in Denmark, a country with generous family leave, mothers faced a penalty of between 5.1% and 5.7% in 2006 (Simonsen & Skipper 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Goldin concluded that gender pay gaps could be explained by career interruptions or flexible schedules. Indeed, childbearing tends to reduce the wage of mothers worldwide (Simonsen and Skipper 2012;ILO 2015c). In Latin America and the Caribbean, Piras and Ripani (2005) studied labor patterns in Bolivia, Brazil, Ecuador, and Peru and found that in 1999, mothers with children age 7 or younger were less likely to have a paid job compared to men or women without children.…”
Section: Ensure That There Are No Differences In Opportunities Acrossmentioning
confidence: 99%
“…Raising children is a key explanation for why women generally earn less than men. Mothers bear most of the costs in terms of lost skills and earnings opportunities when education and careers are interrupted (Adda, Dustmann, & Stevens, ; Kleven, Landais, & Søgaard, ; Nielsen, Simonsen, & Verner, ), whereas fathers experience child premia (Simonsen & Skipper, ). Early parenthood may have worse consequences because of its characteristics: Pregnancy is more often unplanned, the family unit is rarely established at the time of conception, and the young parents are at a critical juncture in life.…”
mentioning
confidence: 99%